Drivers of corporate sustainability – perspectives from organizations in Malaysia. - Khan, Isbah (2018)
This report presents findings about Drivers of Corporate Sustainability – Perspectives from organizations in Malaysia. As there is a growing push for business organizations to develop and inculcate sustainability aspects into business strategies through different actors around the globe – in the case of Malaysia, the government has been committed to reporting on the UN Sustainable Development Goals (SDG) and the stock exchange. According to a survey carried out by KPMG (2015) the quality of Corporate Sustainability reporting improved in the Asia Pacific region by 52% in 2015 as opposed to 50% in 2013, moreover Malaysia has obtained the highest rating at 99% in respect to this survey’s findings related to countries that report CS activities on an annual basis. This makes it necessary to examine and understand the driving forces behind organizations in the country to behave responsibly. Findings show that, CS activities became more popular in Malaysia since the past 10 years. They also point out, internally Human Resources and developing a CS oriented organizational culture are primary drivers, whilst external drivers are customers’ demands and company’s imagery which complements with other drivers like budgets allocated only for CS activities and tax exemptions. This study further proposes to identify which driver has a higher impact, internal or external; and seeks out the role of leadership in terms of promoting CS practices not only internally but also externally.